Preocupación ambiental entre población universitaria : representaciones sociales e implicación personal en temas ambientales en la Universidad de Antioquia (2014)
ABSTRACT: This article, derived from research, shows the difficulties identified in the Citadel of the University of Antioquia when it comes to constructing a definition of the environment in which the human being, as an integral part, must be included. For this purpose, two surveys were applied, the first one which was called “a pilot test” served to refine the questions used in the field of psychology in addressing environmental concerns, this is, the Likert scale; the second one, was a refined survey that was applied among employees, teachers, and students, at the University Campus, which offered the elements needed to analyze the social representations comprising the assessment of environmental problems, the level of personal involvement, and the capacity of action, allowing a reading from the anthropological perspective of relationships between humans and the environment in this social context.